Identification of key sensory attributes of sambal-terasi, impact of different type of terasi, chemical characteristics and salt addition - Ambarita, Mery Tambaria Damanik; Raes, Katleen; De Meulenaer, Bruno (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research studied the identification of key sensory attributes of sambal-terasi as caused by the use of different types of terasi and by the chemical characteristics of terasies, including the addition of salt. Sambal-terasi is a chili sauce containing terasi, a fermented salty seafood from Indonesia. Six different types of terasi, with varying chemical characteristics, including proximate compositions, salt content, free amino acids, biogenic amines, and short chain fatty acids, were prepared as sambal-terasi (at 6%, fresh weight of terasi). To five sambal-terasies table salt was added, aiming to reach a comparable salt content as the sambal-terasi with the highest salt content among the six mentioned sambal-terasies. Eighty-seven un-trained panelists assessed the sambal-terasies’ acceptability in a hedonic test and nine trained panelists rated their intensities towards the attributes sweet, bitter, salty, sour, umami, fishy and rebon. The addition of different types of terasies significantly affected the sensory characteristics of sambal-terasies. The undesirable compounds formed during production of terasi (biogenic amines and short chain fatty acids) could still be perceived in sambal-terasi, therefore their presences should be controlled. Salty, umami and rebon were identified as desirable taste/flavor attributes which were enhanced by the addition of salt. Bitterness was identified as an undesirable taste attribute, which could be reduced by the addition of salt. A salt content of 2-2.5% in sambal-terasi was tentatively proposed as a good compromise with respect to the sensorial aspects and salt intake.